Efficiency of two-member crews in delivering prehospital advanced life support cardiopulmonary resuscitation: A scoping review - Keselica, Miroslav; Peřan, David; Renza, Metoděj; Duška, František; Omáčka, David; Schnaubelt, Sebastian; Lulic, Ileana; Sýkora, Roman (Resuscitation plus, 2024)
BACKGROUND: Advanced Life Support (ALS) during cardiopulmonary resuscitation (CPR) for out-of-hospital cardiac arrest (OHCA) is frequently administered by two-member crews. However, ALS CPR is mostly designed for larger crews, and the feasibility and efficacy of implementing ALS guidelines for only two rescuers remain unclear. OBJECTIVE: This scoping review aims to examine the existing evidence and identify knowledge gaps in the efficiency of pre-hospital ALS CPR performed by two-member teams. DESIGN: A comprehensive search was undertaken across the following databases: PubMed, Web of Science, SCOPUS, Cochrane Library Trials, and ClinicalTrials.gov. The search covered publications in English or German from January 1, 2005, to November 30, 2023. The review included studies that focused on ALS CPR procedures carried out by two-member teams in adult patients in either simulated or clinical settings. RESULTS: A total of 22 articles were included in the qualitative synthesis. Seven topics in two-person prehospital ALS/CPR delivery were identified: 1) effect of team configuration on clinical outcome and CPR quality, 2) early airway management and ventilation techniques, 3) mechanical chest compressions, 4) prefilled syringes, 5) additional equipment, 6) adaptation of recommended ALS/CPR protocols, and 7) human factors. CONCLUSION: There is a lack of comprehensive data regarding the adaptation of the recommended ALS algorithm in CPR for two-member crews. Although simulation studies indicate potential benefits arising from the employment of mechanical chest compression devices, prefilled syringes, and automation-assisted protocols, the current evidence is too limited to support specific modifications to existing guidelines.